2005
DOI: 10.1210/jc.2004-1629
|View full text |Cite
|
Sign up to set email alerts
|

Guide to Bone Health and Disease in Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is the most common genetic disease within the Caucasian population and leads to premature respiratory failure. Approximately 60,000 individuals are currently living with CF in North America and Europe, 40% of whom are adults. The life span of these patients has increased from approximately 2 to 32 yr of age over the last three decades. Bone disease has emerged as a common complication in long-term survivors of CF. Some studies have observed that 50-75% of adults have low bone density and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
389
1
37

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(440 citation statements)
references
References 65 publications
13
389
1
37
Order By: Relevance
“…These efforts culminated in the 2005 publication of the guidelines from the CFF Consensus Conference on Bone Health in which detailed recommendations for screening and treatment of vitamin D deficiency were outlined (17). Conference leaders based treatment recommendations on experience in individuals without CF and stated that the recommendations may need to be revised as CF-specific data became available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts culminated in the 2005 publication of the guidelines from the CFF Consensus Conference on Bone Health in which detailed recommendations for screening and treatment of vitamin D deficiency were outlined (17). Conference leaders based treatment recommendations on experience in individuals without CF and stated that the recommendations may need to be revised as CF-specific data became available.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the growing concern about bone disease in CF, the U.S. Cystic Fibrosis Foundation (CFF) convened a panel of experts to develop consensus treatment guidelines to optimize CF bone health, and these recommendations were recently published (17). The guidelines contained several specific recommendations regarding vitamin D. First, greater attention to maintaining adequate serum 25-OHD levels should occur, with levels being checked annually in the late fall with the goal of maintaining serum 25-OHD between 30 and 60 ng/ml (75-150 nmol/L).…”
mentioning
confidence: 99%
“…To some extent, this does seem to be justified, because BMD reflects bone health over the lifetime of the patient, and current vitamin D concentrations may fluctuate from season to season. 1,25 On the other hand, both parameters are simply related to LM. Nonetheless, the use of logistic regression for analysis of the study results has shown the strong relationship of BMD with both body weight (Po0.025) and LM (Po0.044).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60 000 individuals with CF are currently living in North America and Europe, 40% of whom are adults. 1 Although bone disease in CF was first described in 1979, 2,3 it has only recently received the proper attention as a result of the increase in life expectancy of CF patients. Their life span has increased from approximately 2 to 37 years of age over the past 3 decades, 4 a time period which allows for the occurrence of bone disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation